1997
DOI: 10.1152/jappl.1997.82.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Sources of error ina- aD O 2 calculated from blood stored in plastic and glass syringes

Abstract: We studied the effects of time delay on blood gases, pH, and base excess in blood stored in glass and plastic syringes on ice and the effects of resulting errors on calculated alveolar-to-arterial PO2 difference (A-aDO2). Matched samples of dog whole blood were tonometered with gas mixtures of 5% CO2-12% )2-83% N2 (mixture A), 10% CO2-5% O2-85% N2 (mixture B), and 2.88% CO2-4% O2-93.12% N2 (mixture C). Tonometered blood samples were transferred to 5-ml glass (5G), 5-ml plastic (5P), and 3-ml plastic (3P) syrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In Experiment 2G, when samples of cystic fluid were collected in glass, we obtained the same results as in Experiment 1 with absolute stability in the differences for all 12 triads of samples. Our results are supported by evidence that syringe material and conditions and length of sample storage, significantly influence acid-base balance values (Szenci and Besser 1990;Wu et al 1997;Beaulieu et al 1999;Knowles et al 2006;Cingi et al 2009). Despite the fact that we have not performed a direct comparison of the samples from the same source stored in glass and plastic syringes, we agree with the assertion that if a delay in acid-base balance analysis is expected, the samples should be drawn and stored in glass (Knowles et al 2006).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In Experiment 2G, when samples of cystic fluid were collected in glass, we obtained the same results as in Experiment 1 with absolute stability in the differences for all 12 triads of samples. Our results are supported by evidence that syringe material and conditions and length of sample storage, significantly influence acid-base balance values (Szenci and Besser 1990;Wu et al 1997;Beaulieu et al 1999;Knowles et al 2006;Cingi et al 2009). Despite the fact that we have not performed a direct comparison of the samples from the same source stored in glass and plastic syringes, we agree with the assertion that if a delay in acid-base balance analysis is expected, the samples should be drawn and stored in glass (Knowles et al 2006).…”
Section: Discussionsupporting
confidence: 84%
“…This procedure is much easier than the recovery of follicular fluid. Nevertheless, for this analysis, there are many potential pre-analytical errors in blood sampling-e.g., caused by the underfilling of the syringe (Bandi 1981;James et al 1997), the syringe material itself or conditions of sample storage (Szenci and Besser 1990;Wu et al 1997;Beaulieu et al 1999;Knowles et al 2006;Cingi et al 2009). Because similar errors should be expected during and after the collection of follicular fluid (Redding et al 2006), requirements for anaerobic follicular fluid collection have been reported (Berg et al 2005;Redding et al 2006).…”
mentioning
confidence: 99%
“…The underfilling of blood collection tubes results in a false decrease of CO 2 concentration in serum and can result in a false diagnosis of metabolic acidosis in dogs and cats (James et al 1997). Acid-base indicators can also be changed by storage temperature or type of syringe (plastic or glass) (Wu et al 1997;Beaulieu et al 1999). Because similar errors should be expected during and after collection of follicular fluid (Redding et al 2006), the requirements for anaerobic follicular fluid collection have been reported (Berg et al 2005;Redding et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of the follicular fluid for acid-base balance (ABB) analysis from live animals has been rarely described (Berg et al 2005;Cech et al 2007) and technical aspects of the procedure were not evaluated. Although peripheral blood collection for ABB analysis is performed routinely and this procedure is easier than the recovery of follicular fluid, many preanalytical errors in blood sampling for this analysis have been described (Bandi 1981;James et al 1997;Wu et al 1997;Beaulieu et al 1999).…”
mentioning
confidence: 99%
“…Several studies have sought to determine the effects of syringe material (plastic vs glass), storage time, and storage temperature on normal ABG and blood oxygen saturation values. 2,3 Results suggest that samples drawn into plastic syringes should be analyzed immediately, that on-ice storage of plastic syringes is ineffective, and that if analysis is going to be delayed, samples should be drawn and stored in glass containers. Although values can change with time in both glass and plastic syringes, errors are most prevalent and consequential when used to calculate the alveolar-to-arterial oxygen difference using the alveolar gas equation.…”
mentioning
confidence: 99%